Photosynthetic metabolism in microphytobenthos : modulation by temperature and dissolved inorganic carbon - Vieira, Sónia Catarina Reis, 1978- (2016)
Tese de doutoramento, Biologia (Ecofisiologia), Universidade de Lisboa, Faculdade de Ciências, 2017